1997
DOI: 10.1002/etc.5620160103
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicology of tropical marine ecosystems

Abstract: Abstract-The negative effects of chemical contaminants on tropical marine ecosystems are of increasing concern as human populations expand adjacent to these communities. Watershed streams and ground water carry a variety of chemicals from agricultural, industrial, and domestic activities, while winds and currents transport pollutants from atmospheric and oceanic sources to these coastal ecosystems. The implications of the limited information available on impacts of chemical stressors on mangrove forests, seagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
139
1
17

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(158 citation statements)
references
References 236 publications
(353 reference statements)
1
139
1
17
Order By: Relevance
“…Ecotoxicological studies on clams have mostly been carried out on juveniles (Blidberg et al 1999;Elfwing et al 2002), where both copper (5 μg Cu2 + l −1 ) and low salinity have been shown to be sub lethal but negatively affect the physiological performance. However, copper concentrations much higher than this has been reported in reef waters (Peters et al 1997). It is very likely that copper in higher concentrations than investigated in this study may further increase the mortality in P. malabarica larvae.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Ecotoxicological studies on clams have mostly been carried out on juveniles (Blidberg et al 1999;Elfwing et al 2002), where both copper (5 μg Cu2 + l −1 ) and low salinity have been shown to be sub lethal but negatively affect the physiological performance. However, copper concentrations much higher than this has been reported in reef waters (Peters et al 1997). It is very likely that copper in higher concentrations than investigated in this study may further increase the mortality in P. malabarica larvae.…”
Section: Discussioncontrasting
confidence: 52%
“…Copper is an anthropogenic pollutant known to be harmful in aquatic environment and several sources such as coastal runoffs and anti-fouling paint affects non-target organisms (Peters et al 1997). Short neck clam, Paphia malabarica (Family: Veneridae) is widely distributed in the Vembanad Lake and Ashtamudi estuary, south west coast of India.…”
Section: Introductionmentioning
confidence: 99%
“…T. testudinum is considered an index or keystone species (Peters et al, 1997) and it and H. wrightii are common to the northwest and southern coasts of Florida (Iverson and Bittaker, 1986). After uprooting and removal of sediments, the plants were thoroughly rinsed at least twice on site with seawater to remove remaining inorganic particles.…”
Section: Media Collectionmentioning
confidence: 99%
“…The contribution of toxic chemicals to seagrass declines, the focus of this study, is largely unknown and has been investigated less frequently than the effects attributable to nutrient enrichment which is considered the primary cause of seagrass declines. However, some consider the impact of anthropogenic chemicals to be significant and worthy of increased investigation (Catsiki and Panayotidis, 1993;Short and Wyllie-Echeverria, 1996;Peters et al, 1997;SchlacherHoenlinger and Schlacher, 1998;Bester, 2000;Ralph, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic activities including industry, urbanisation and land development (agriculture and mining) are having a major impact on tropical coasts through an increase in sedimentation and input of nutrients and chemical contaminants (Peters et al 1997). Tropical ecosystems are valuable and unique, with greater than 80% of the global ecological diversity found in these regions (Biodiversity Futures, JCU 2015).…”
Section: Introductionmentioning
confidence: 99%